Altered glutamine metabolism in breast cancer: subtype dependencies and alternative adaptations - El Ansari, Rokaya; McIntyre, Alan; Craze, Madeleine L.; Ellis, Ian O.; Rakha, Emad A.; Green, Andrew R. (Wiley, 2017)
Cancer cells must alter their metabolism in order to satisfy the demands of necessary energy and cellular building blocks. These metabolic alterations are mediated by many oncogenic changes that affect cellular signalling pathways, which result in sustained cell growth and proliferation. Recently, metabolomics, has received great attention in the field of cancer research and as the essential metabolic pathways that drive tumour growth and progression are determined, the possibilities of new targets for therapeutic intervention are opened. More specifically, as breast cancer is a heterogeneous disease there is growing evidence that differences in metabolic changes exist between molecular subtypes. In this review, the most recent findings in breast cancer cell metabolism are discussed, with particular emphasis on glutamine and its transporters which is considered one of the key amino acids fuelling cancer growth. Furthermore, the metabolic differences between the molecular subtypes of breast cancer are examined, highlighting the clinical utility for breast cancer diagnosis and treatment.